Fractal characterization of gait in parkinson's disease using detrended fluctuation analysis - Uning, R.; Abu Osman, Noor Azuan; Usman, J.; Wan Abas, Wan Abu Bakar (2007)
Fractal analysis of physiological time series have revealed many interesting features that were not so easily identified using conventional techniques 1. For example, altered gait dynamics has been reported for subjects with Huntingtons disease (HD) in comparison to healthy controls 2. Studies also showed that stride-interval fluctuations are more random in elderly subjects and in subjects with HD, which are apparently associated with changes in central nervous system control. In this paper, we perform fractal analysis on subject with Parkinsons disease (PD) using detrended fluctuation analysis (DFA)